2021
DOI: 10.1029/2021gl094805
|View full text |Cite
|
Sign up to set email alerts
|

Diel Redox Cycle of Manganese in the Surface Arctic Ocean

Abstract: Manganese (Mn) is the third most abundant transition metal in Earth's crust and exists in three oxidation states (II, III, and IV) in the ocean. Mn is an essential element to life and used to catalyze the oxidation of water to O 2 in Photosystem II (Yano et al., 2006) by phytoplankton, and to detoxify cells from superoxide radicals via the antioxidant enzyme Mn superoxide dismutase (Peers & Price, 2004). Oxidation from dissolved Mn(II) to particulate Mn(III/IV) oxides is known to proceed through two sequential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…This phenomenon suggests an unknown formation pathway of OICs in frozen environments under neutral conditions, which is different from the iron­(III)-based systems. Manganese species can enter the Arctic Ocean from rivers or coastal erosion and be trapped in frozen media (glacier, sea ice, and atmospheric ice particle) in the Arctic region. , Xiang et al reported that particulate manganese oxidation states were more reduced in the day and more oxidized at night in the surface Arctic Ocean, which indicated that the Mn redox cycle frequently occurred in the polar region. On the other hand, NOM and MnO 2 are more abundant in the terrestrial environments than in the marine environment, and the terrestrial media such as soil and sediments may undergo freezing or freeze–thaw cycles in winter.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon suggests an unknown formation pathway of OICs in frozen environments under neutral conditions, which is different from the iron­(III)-based systems. Manganese species can enter the Arctic Ocean from rivers or coastal erosion and be trapped in frozen media (glacier, sea ice, and atmospheric ice particle) in the Arctic region. , Xiang et al reported that particulate manganese oxidation states were more reduced in the day and more oxidized at night in the surface Arctic Ocean, which indicated that the Mn redox cycle frequently occurred in the polar region. On the other hand, NOM and MnO 2 are more abundant in the terrestrial environments than in the marine environment, and the terrestrial media such as soil and sediments may undergo freezing or freeze–thaw cycles in winter.…”
Section: Resultsmentioning
confidence: 99%
“…As removal of Cr in subsurface waters at our study sites, where lithogenic suspended particles are abundant, appears to proceed via scavenging of Cr(III) by colloid aggregates that consist of authigenic Fe-(oxyhydr)oxides and/or dust particles (Section 4.2), increased concentrations of dissolved Cr in intermediate waters could be due to re-oxidation of Cr(III) to the less particle reactive Cr(VI), potentially driven by reduction (and dissolution) of manganese (III, IV) oxides (MnO x ) that are present throughout the oxygenated water column (Jones et al, 2020). However, as concentrations of particulate Mn are very low (sub-nanomolar) in oceanic environments (Jones et al, 2020;Xiang et al, 2021), the predicted oxidation rate of Cr(III) is extremely slow, ~2 × 10 -5 nmol kg -1 yr -1 (van der Weijden and Reith, 1982). The residence time of fine lithogenic mineral particles (~1 to 5 mm diameter) in the upper 2000 m of the North Atlantic Ocean water column is months to years (Ohnemus and Lam, 2015;Ohnemus et al, 2019), over which time oxidation of Cr(III) can be expected to increase the Cr concentration of seawater by approximately 10 -5 to 10 -4 nmol kg -1 in the intermediate waters.…”
Section: Regeneration Of Cr In Deeper Watersmentioning
confidence: 99%
“…Bulk measurements can also be used on heterogeneous samples to determine average speciation or redox states of the area illuminated. This can be a good strategy for determining large-scale changes in the environment (Lam and Bishop, 2008;Lee et al, 2021;Xiang et al, 2021).…”
Section: Guidance For Successful Synchrotron Analysismentioning
confidence: 99%